1997
DOI: 10.1210/jc.82.5.1582
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Stimulates Cytokine Production by Villous Explants from the Human Placenta

Abstract: It has been hypothesized that inadequate placentation in the hypertensive disorder of pregnancy known as preeclampsia creates foci of placental ischemia/hypoxia leading to the elaboration of factors that compromise systemic endothelial function to produce disease sequelae. As tumor necrosis factor-alpha (TNF alpha) and interleukin-1 (IL-1) are inflammatory cytokines capable of eliciting endothelial cell dysfunction, we investigated whether the production of these inflammatory cytokines by cultured villous expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
3
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 0 publications
3
114
3
2
Order By: Relevance
“…The source of increasing IL-6 in maternal plasma remains unknown [73,74], but several studies found that the placenta is not the source. Our research showed that miR-181a induced expression of IL-6 in MSCs but not in trophoblast cells (data not show).…”
Section: Discussionmentioning
confidence: 99%
“…The source of increasing IL-6 in maternal plasma remains unknown [73,74], but several studies found that the placenta is not the source. Our research showed that miR-181a induced expression of IL-6 in MSCs but not in trophoblast cells (data not show).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is known to increase XDH/XO 26 and is increased in conditioned media from cytotrophoblast and villous explants cultured under hypoxic conditions in vitro. 27 There is also a report of increased TNF-␣ production by preeclamptic placentas. 28 If hypoxia is a stimulus, then it is perhaps not surprising that invasive cytotrophoblast, with oxygenation determined by nonanastamosing basal arteries and diffusion through several cell layers of decidua, would be affected whereas villous cytotrophoblast exposed to extensively comingled intervillous blood flow would not.…”
Section: Discussionmentioning
confidence: 99%
“…19 Whether placental hypoxia causes the high TNF-␣ in maternal plasma is less clear. 18 However, despite apparent placental hypoxia in eNOS KO(ko) pregnancies ( Figure 5), there were no significant increases in placental sFlt1 or TNF-␣ mRNA levels ( Figure 5B and 5C). Maternal plasma sFlt1 ( Figure 5A) was not elevated in pregnant eNOS KO(ko) mice, whereas it is often elevated in women with preeclampsia.…”
Section: Maternal Plasma Sflt1 Levels and Placental Expression Of Sflmentioning
confidence: 92%
“…Hypoxia increases placental production of the antiangiogenic factor, sFlt1, 17 and the inflammatory cytokine, TNF-␣, 18 in human placental explants. Placental hypoxia is thought to cause the elevation in sFlt1 in maternal plasma in preeclamptic pregnancies.…”
Section: Maternal Plasma Sflt1 Levels and Placental Expression Of Sflmentioning
confidence: 97%